Nuclear factor kappa B is required for the production of infectious human herpesvirus 8 virions - Blattman, Negin N.; Lagunoff, Michael; Blattman, Joseph N.; Corey, Lawrence (Frontiers in Microbiology, 2014)
Human herpesvirus 8 (HHV8) infection leads to potent activation of nuclear factor kappa B (NFκB) in primary and transformed cells. We used recombinant HHV8 (rKSHV.219) expressing green fluorescent protein under the constitutive cellular promoter elongation factor 2α and red fluorescent protein under an early HHV8 lytic gene promoter T1.1 to monitor replication during infection of human foreskin fibroblasts (HF), noting changes in NFκB activity. In primary HF, NFκB levels do not affect the ability of HHV8 to establish infection or maintain latency. Furthermore, there was no effect on the percent of cells undergoing reactivation from latency, and there were similar numbers of released and cell-associated HHV8 viral particles following reactivation in the presence of inhibitors. Reactivation of HHV8 in latently infected HF in the presence of NFκB inhibitors resulted in production of viral particles that did not efficiently establish infection, due to deficiencies in binding and/or entry into normally permissive cells. Exogenous expression of glycoprotein M, an envelope protein involved in viral binding and entry, was able to partially overcome the deficiency induced by NFκB inhibitors. Our data indicate that in primary cells, NFκB is not required for infection, establishment of latency, or entry into the lytic cycle, but is required for the expression of virion associated genes involved in the initial steps of virion infectivity. These studies suggest that strategies to inhibit NFκB may prevent HHV8 spread and should be considered as a potential therapeutic target for preventing HHV8 associated diseases.